2011
DOI: 10.1186/1471-2156-12-68
|View full text |Cite
|
Sign up to set email alerts
|

Genome evolution in the fish family salmonidae: generation of a brook charr genetic map and comparisons among charrs (Arctic charr and brook charr) with rainbow trout

Abstract: BackgroundSalmonids are regarded as 4R derivative species, having experienced 4 whole genome duplication events in their ancestry. Many duplicated chromosome regions still share extensive homology with one another which is maintained primarily through male-based homeologous chromosome pairings during meiosis. The formation of quadrivalents during meiosis leads to pseudolinkage. This phenomenon is more prevalent within 5 of the 12 ancestral teleost linkage groups in salmonids.ResultsWe constructed a genetic lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 44 publications
3
63
0
Order By: Relevance
“…Perhaps most intriguing is the presence of an eight gene cluster spanning 3.022 Mb along Ga-XIX. Unfortunately, due to the low resolution of the Arctic charr linkage map (9,63,69), the precise location of this cluster in Arctic charr is difficult to ascertain. Possible locations include AC-1, 4, 6, 12, and 19; however, most of these linkage groups are implicated by single marker associations (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps most intriguing is the presence of an eight gene cluster spanning 3.022 Mb along Ga-XIX. Unfortunately, due to the low resolution of the Arctic charr linkage map (9,63,69), the precise location of this cluster in Arctic charr is difficult to ascertain. Possible locations include AC-1, 4, 6, 12, and 19; however, most of these linkage groups are implicated by single marker associations (48).…”
Section: Discussionmentioning
confidence: 99%
“…On these occasions, synteny maps of stickleback with Atlantic salmon and rainbow trout (48) were used in the same manner to make predictions about gene positions in those species. Known homologous linkage group affinities among Arctic charr, Atlantic salmon, and rainbow trout (9,10,63) were then used to make predictions about the position of differentially expressed genes on the Arctic charr linkage map.…”
Section: Methodsmentioning
confidence: 99%
“…A genetic linkage map for Canadian brook trout [Timusk et al, 2011] mapped the SD to a linkage group corresponding to AC-4, the sex linkage group in Arctic char, so there may be more than one location of SD in this species as well. It is interesting that lake and brook trout form totally interfertile hybrids and that F1 hybrids between [Moghadam et al, 2007].…”
Section: Salvelinusmentioning
confidence: 99%
“…We found that stickleback synteny blocks on Arctic charr linkage groups AC-1, AC-11 [henceforth referred to as AC-1/11, due to the strong homeologous affinities of these linkage groups (Danzmann et al, 2005;Timusk et al, 2011;Norman et al, 2012)], and AC-28 contain a greater number of DEGs than expected by chance. These linkage groups also contain QTL for the salinity tolerance performance traits Na + /K + -ATPase activity and growth in seawater , suggesting that these QTL could be the product of multiple genes containing cisregulatory polymorphisms.…”
Section: Research Articlementioning
confidence: 87%
“…This would have to be temporary, however, perhaps until gill tissue and other ionoregulatory organs have transitioned to an optimal ion-excreting state, because the seawater phase of salmonid ontogeny is typically characterized by heightened growth rates. Repression of developmental gene expression may liberate energy for the transition of osmoregulatory tissues towards an ion-excreting state, as the metabolic demand of hypo-osmoregulation can be high, ranging from <4% in cut-throat trout (Oncorhynchus clarkii clarkii) (Timusk et al, 2011); stickleback chromosomes obtained from Ensembl (version 68) (Jones et al, 2012;Flicek et al, 2013); synteny block sizes obtained from Norman et al (Norman et al, 2012); numbers in parentheses for family 10 (F10) and family 12 (F12) differentially expressed genes (DEG) represent expected values from a 2×2 χ 2 test for independence; bold values are significant at P<0.05; *values pass FDR significance threshold (α=0.05). (Morgan and Iwama, 1999) to 30% in rainbow trout (Rao, 1968), and 20% of gill metabolism in Atlantic salmon (McCormick et al, 1989).…”
Section: Research Articlementioning
confidence: 99%